(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines one of the fundamental issues of classical Arabic linguistics the syntactic function of the munodo (the vocative). As the object of the study, two important commentaries on Mahmud al-Zamakhshari’s renowned work al-Mufassal were selected: at-Takhmir by Qosim al-Khwarizmi and al-Iqlid by Umar al-Jandi. The article comparatively analyzes the distinctive scholarly views of both linguists regarding the munodo, its position within the sentence, its governing elements (awomil), and its syntactic relationships.